(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
People’s daily lives were significantly affected by the COVID-19 outbreak in the first half of 2020.As a result, people have been forced to live apart, the global economy has been disrupted, and there hasbeen limited access to medical and psychological therapy. Even though these measures are necessaryto stop the virus from spreading, the negative effects on health, mental well-being, and society areobvious. In early 2020, the United States was hit by an epidemic of coronavirus disease 2019 (COVID-19),which led to more severe sequelae, a higher death rate among the elderly, and a larger concern thatisolation would worsen existing mental health disorders among the older population. As a result of theepidemic’s widespread nature, older people were concerned about the potential for a mental health crisisamong themselves, despite having lower stress reactivity than younger people. Communication withloved ones and caregivers has grown more difficult for the elderly, both at home and in nursing homes.This study was structured as a concurrent embedded mixed method research to look at sadness,anxiety, and stress in older people after they have had a heart attack. This approach seeks to embed ornest both (QUAN qual) data types at the same time, with one kind of data serving as a supporter.